Cost accounting : principles and procedural applications - Guerrero, Pedro D. (Manila, Philippines : GIC Enterprises & Co. Inc., 2010)
This volume covers the principles and applications of Job Order Cost Accounting. The book opens with an overview of the nature and purpose of cost accounting.
Chapter 1. Cost Accounting - Basic concepts and the job order cost cycle -- Chapter 2. Purchasing materials -- Chapter 3. Storing and issuing materials -- Chapter 4. Controlling and costing Materials Inventory -- Chapter 5. Labor Accounting - control and costing -- Chapter 6. Manufacturing overhead accounting - Actual and Applied -- Chapter 7. Manufacturing Overhead - Departmentalization -- Chapter 8. Activity based - Costing -- Chapter 9. Completing the cost cycle and accounting for production losses.
Keywords: COST ACCOUNTING